2012
DOI: 10.4103/0976-0105.105335
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the central and peripheral analgesic and anti-inflammatory activity of Draksharishta an Indian Ayurvedic formulation

Abstract: Rationale: Draksharishta (DRK) is an Ayurvedic formulation approved by the "National formulary of Ayurvedic Medicine 2011", of Bangladesh. It is widely available in the Bangladeshi market as an effective preparation to treat lumbago, sciatia and arthritic pain of joints. But there are very scienti ic evidences available to support their common uses. Objectives: Our present studies make an attempt toward identifying probable antinociceptive and anti-in lammatory effect and its mechanisms of DRK. Findings: DRK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Based on these findings, we inferred that the anti-inflammation of Malyngamide F may be mediated by suppressing the production of IL-6 and TNF- α . On the other hand, convincing evidence has indicated that PGE-2 can cause abdominal constriction, and it is mostly responsible for causing inflammatory pain [ 35 , 36 ]. Several flavonoids have been demonstrated to produce analgesic action through suppression of PGE-2 synthesis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, we inferred that the anti-inflammation of Malyngamide F may be mediated by suppressing the production of IL-6 and TNF- α . On the other hand, convincing evidence has indicated that PGE-2 can cause abdominal constriction, and it is mostly responsible for causing inflammatory pain [ 35 , 36 ]. Several flavonoids have been demonstrated to produce analgesic action through suppression of PGE-2 synthesis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formalin test was carried out as described previously. [ 12 16 ] Each animal was assigned and acclimatized to one of 20 formalin test chambers (a perspex chamber 15 cm × 15 cm × 15 cm) for 30 min before formalin injection. Male mice were then pretreated with vehicle (10 ml/kg of 0.9% NaCl, i.p), XA (10–100 mg/kg, p.o.)…”
Section: Methodsmentioning
confidence: 99%